A Cross-Disciplinary Project-Based Learning to Raise Indonesian Students’ Awareness of Natural Disasters - da Silva, Anna Marietta; Helnywati, Helnywati (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2021)
The present study aims at raising young students’ awareness of natural disasters through a cross-disciplinary multimodal project-based learning method using Vygotsky’s (1986) socio-cultural approach. An Art project was carried out by second-grade students of one private bilingual school in Jakarta. The project, which was group work, included discussing which objects could save lives from the disaster, drawing the objects, and presenting the work in front of the class. All discussions and presentations were audio recorded. The objects and the recording were then analysed to identify students’ knowledge about surviving three common natural disasters in Indonesia, i.e., earthquake, tsunami, and volcanic eruption. The findings indicate that the students have an initial knowledge about how to survive the disasters, but their literacy on disaster mitigation is still low. It is recommended that literacy on natural disasters should be part of the curriculum and implemented consistently.